Dissolution‐Enhanced Luminescent Bioassay Based on Inorganic Lanthanide Nanoparticles1. (11th August 2014) - Zhou, Shanyong; Zheng, Wei; Chen, Zhuo; Tu, Datao; Liu, Yongsheng; Ma, En; Li, Renfu; Zhu, Haomiao; Huang, Mingdong; Chen, Xueyuan
Abstract Conventional dissociation‐enhanced lanthanide fluoroimmunoassays (DELFIA) using molecular probes suffer from a low labeling ratio of lanthanide ions (Ln3+) per biomolecule. Herein, we develop a unique bioassay based on the dissolution‐enhanced luminescence of inorganic lanthanide nanoparticles (NPs). As a result of the highly concentrated Ln3+ ions in a single Ln3+ NP, an extremely high Ln3+ labeling ratio can be achieved, which amplifies significantly the luminescence signal and thus improves the detection sensitivity compared to DELFIA. Utilizing sub‐10 nm NaEuF4 NPs as dissolution‐enhanced luminescent nanoprobes, we demonstrate the successful in vitro detection of carcinoembryonic antigen (CEA, an important tumor marker) in human serum samples with a record‐low detection limit of 0.1 pg mL−1 (0.5 fM). This value is an improvement of approximately 3 orders of magnitude relative to that of DELFIA. The dissolution‐enhanced luminescent bioassay shows great promise in versatile bioapplications, such as ultrasensitive and multiplexed in vitro detection of disease markers in clinical diagnosis.